2013
DOI: 10.1097/brs.0b013e31828cb001
|View full text |Cite
|
Sign up to set email alerts
|

Routine Imaging for Elective Lumbar Spine Surgery

Abstract: Findings highlight extreme variability in practice associated with a notable lack of standard of care and provide a baseline for utility studies that may lead to more evidence-driven care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, prior, similar studies have not shown any association between geographic location and imaging practices. 8,9 Another limitation is that this data, which was based on self-report, may not be as reliable as data collected directly from a large series of hospital systems or physician groups or data extracted from a review of a series of surgeons' records. Because these data are based on self-report, there is the significant potential that errors in surgeons' memories and estimations could have biased results.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior, similar studies have not shown any association between geographic location and imaging practices. 8,9 Another limitation is that this data, which was based on self-report, may not be as reliable as data collected directly from a large series of hospital systems or physician groups or data extracted from a review of a series of surgeons' records. Because these data are based on self-report, there is the significant potential that errors in surgeons' memories and estimations could have biased results.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of obtaining radiographic images past the index operation during postoperative hospital stay remains contentious among surgeons. In a survey of spine surgeons, 54% indicated they order postoperative imaging after surgery before discharge 1 . Furthermore, the majority ordered routine postoperative imaging even with adequate intraoperative images of the patient's final construct 1 .…”
mentioning
confidence: 99%
“…In a survey of spine surgeons, 54% indicated they order postoperative imaging after surgery before discharge 1 . Furthermore, the majority ordered routine postoperative imaging even with adequate intraoperative images of the patient's final construct 1 . Evidence suggests there is no detectable movement of implanted hardware in the immediate postoperative period, 2,3 raising doubts on the utility of immediate postoperative imaging, especially in the setting of adequate intraoperative films of the hardware.…”
mentioning
confidence: 99%